Impact of Micro-Finance on Income Change of Women in Chandragiri Municipality - Acharya, Gyanu (Tribhuvan University Journal, 2020)
This study aims to analyze the impact of micro-finance in income change of members of Women Co-operative Society (WCS). The study is based on both primary and secondary data. For this, 112 WCS' women of Thankot Branch were taken as population and among them 56 loan borrower members were randomly selected as sample of the study. The primary data were collected through a setoff questionnaire. Secondary data were collected from the documents of WCS, Central Bureau of Statistics, Finance Ministry, the Government of Nepal. Different research reports, books and journals were also consulted as sources of secondary data. The collected data were analyzed by presenting them on tables and interpreted through percentage. The findings of the study show that the average monthly income of borrowers has increased by 31.14 percent after intervention of micro finance programme. Similarly, the average monthly income of the households has increased by 9.43 percent (21.71 percent difference between borrowers and households). All these show that WCS micro-finance program has contributed to the change in economic status of women by increasing their income.